2001
DOI: 10.15807/jorsj.44.1
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete Bass Model and Its Parameter Estimation

Abstract: Abst,raet A discrete Bass model, which is a discrete analog of the Bass model, is proposed. This discrete Bass rnodel is defined as a difference equation that has an exact solution, The difference equation and the solution respectively t,elld to the differential equation whic:h the Bass model is defined as and the solution when the time interval tends to zero. The discrete Bass model conserves the characterist,ics of the Bass model because the differem, ce equation has am exact solution. Therefore, the discret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 18 publications
0
37
0
2
Order By: Relevance
“…Consequently, Bass (1969) incorporated the new 'innovator perspective' in the Mansfield model. Bass assumes that diffusion is determined not only by 'imitators' but also by 'innovators' (Satoh, 2001). Thus the Bass specification is also labelled a 'mixed-information-source' model.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, Bass (1969) incorporated the new 'innovator perspective' in the Mansfield model. Bass assumes that diffusion is determined not only by 'imitators' but also by 'innovators' (Satoh, 2001). Thus the Bass specification is also labelled a 'mixed-information-source' model.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, according to the model, the innovators and imitators participate in the acceptance of new services, and new users are formed when innovators communicate about their experiences to imitators. The model is mathematically explained by the following formulas [15]: …”
Section: Forecasting a New Postal Service Demandmentioning
confidence: 99%
“…or using the analogy with another service for which parameters p and q are known. The latter way, after the introduction of a new service, is to assess p and q parameters by using various mathematical techniques from which the most known are [15]: Ordinary least squares, Maximum likelihood estimation, Non-linear least squares.…”
Section: Calculation Of the Bass Diffusion Parametersmentioning
confidence: 99%
“…The exact solution of the above difference equation is given by: (6) Similarly, using the Satoh [15] approach, another discrete equivalent of a continuous model (3) can be obtained. Again, it can be shown that as 0 → δ , m(n) given by (6) and (7) converge to the corresponding continuous SRGM given by (3).…”
Section: Other Discrete Srgmsmentioning
confidence: 99%
“…Two other discrete equivalents of the Kapur and Garg [6] model are also included: these exist in the literature due to Innoue [19] and Satoh [15]. They are subsequently shown to be equivalent to a discrete equivalent of Kapur and Garg [6] that is mathematically and computationally much simpler.…”
Section: Introductionmentioning
confidence: 99%